The relationship between corporate governance and tax avoidance - evidence from Germany using a regression discontinuity design - Dirk Kiesewetter; Johannes Manthey (Arbeitskreis Quantitative Steuerlehre (arqus), 2017)
This paper analyses the relationship between corporate governance and tax avoidance. We use a regression discontinuity design (RDD) in a two-stage instrumental variable and take advantage of the exogenous variation in the index membership around the DAX and MDAX threshold. We suppose the differences in corporate governance result from the valueweighted composition of the market capitalization-based indexes. We find a significant discontinuity in the level of the corporate governance characteristics at the cutoff. The largest MDAX firms show stronger corporate governance characteristics compared to the smallest DAX firms. Our analysis shows that strong corporate governance characteristics drive down the effective tax rate for the DAX firms. This paper contributes to existing research by establishing a causal relationship between governance and taxes. This research aims to highlight the wide-ranging effects of institutional investors, which channel in corporate policy, in our case tax management.
Keywords: H20; H25; H26; M41; M48; 330; Tax Avoidance; Corporate Governance; RDD; Regression Discontinuity Design